Prototipe Penstabil Tegangan Listrik Berbasis ESP32 dengan Transformator Center Tap (CT) dan Monitoring via Blynk untuk Perangkat Elektronik Rumah Tangga - Nicholas Adrian; Joko Purnomo; Alona Situmeang (CYCLOTRON, 2026)
Fluctuations in PLN electricity voltage often cause undervoltage conditions below the SNI standard (198–242 V), which can reduce performance and damage household electronic devices. This study aims to design a single-phase automatic voltage stabilizer prototype that is capable of increasing low voltage to approach 220 V and can be monitored through a smartphone application. The prototype uses a PZEM-004T sensor to detect voltage as a control reference, an ESP32 microcontroller as the control center, a Center Tap (CT) transformer configured in series as a booster to stabilize the voltage, and a relay as an output tap selector. Testing was conducted with input voltage variations of 170–220 V, and the results showed that at an input of 170 V, the output could be stabilized at 224.9 V. This value is still within the ±10% tolerance range of the nominal voltage of 220 V. Based on these results, the prototype proved capable of maintaining voltage stability under undervoltage conditions and providing a safe output for household electronic devices.